Utilization and Conversion of Discarded Lobster Shells into Valuable Biopolymers - A Pilot Study - Raj, Aishwarya Lakshmi Thasvanth; John, Rinish Mortin; Deepakraj, Sesvi; Dinakarkumar, Yuvaraj (Journal of Sustainability and Environmental Management, 2022)
Chitin is one of the most abundant polysaccharides and can be made by combining shells of crabs, shrimp, lobsters, and fish. This study used discarded lobster shells as a raw material to produce a biopolymer. As part of the process, TiO2 was incorporated into the film in order to increase tensile strength. As compared to the control sample without TiO2 (3.34 MPa), the experimental sample with TiO2 showed improved tensile strength (3.96 MPa). Bio composites containing chitin and chitosan have been shown to produce thin, labile, textured films with good apparent textures. Upon tensile testing, it was determined that the material produced was sturdy enough for use as packaging and medical equipment. The prepared samples were analyzed in a variety of ways to understand their properties. In the FTIR analysis, it is evident that certain functional components are present that are responsible for the plasticity of the material. A study conducted on pathogenic Escherichia coli and Staphylococcus aureus indicated that the film had antimicrobial properties, as indicated by the zone of inhibition between 13 mm and 11 mm in samples with TiO2, respectively, and 11 mm and 10 mm in samples without TiO2. According to the physical degradation test, the produced biopolymer was 100% degraded when compared to a synthetic plastic (12%), which makes it the best choice for creating a multipurpose material. In addition to its biodegradability, biocompatibility, and anti-microbial properties, this material is suitable for use as biomedical interfaces and packaging materials.